ANALISIS KETERAMPILAN BERTANYA SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA MATERI NEGARAKU INDONESIA KELAS IV A SDN SARIREJO - Cicik Sulistya; Fine Reffiane; Arfilia Wijayanti; Karunia Suhono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The aim of the study was to identify and describe the skills of asking questions in learning Pancasila Education Materials Negaraku Indonesia class IV A SDN Sarirejo. This research was conducted with descriptive research using a qualitative research approach. The research was conducted at Sarirejo Elementary School which is located at Jalan Kartini number 151, Sarirejo Village, East Semarang District, Semarang City, Central Java Province. The data collection technique in this study was triangulation, namely observation, interviews, and documentation. The analysis technique used is data reduction, data reduction, and data presentation. The results showed that according to the indicators in the instrument there were 4 points, namely brief and clear, focused, probable or diverging and had clear innotations. Students are more prominent in the short and clear aspects, the sub-aspect of students submitting questions using good and correct Indonesian, there are 18 students who are visible. In the results of the presentation of questioning skills, there were 20 students who were less skilled at asking questions with a percentage of 71%, 5 were quite skilled at asking questions with a percentage of 18%, 3 students were skilled at asking questions with a percentage of 11% and 0% or students who had very skilled skills in asking questions had not yet been seen. Then, from the results of the interview with the class IV A teacher, it was found that the skills of the students in class IV A were that students who asked questions were only those who excelled, other students still liked to play with colleagues, were shy, and were afraid of being made fun of by friends so that it could be concluded that the questioning skills of class IV A in learning Pancasila education material Negaraku Indonesia SDN Sarirejo varied.